2019
DOI: 10.1155/2019/6076923
|View full text |Cite
|
Sign up to set email alerts
|

Successful Resolution of a Large Left Atrial and Left Atrial Appendage Thrombus with Rivaroxaban

Abstract: A 79-year-old male was admitted to the hospital for acute exacerbation of heart failure. The patient had history of atrial fibrillation and was planned for cardioversion. Preprocedure transesophageal echocardiogram (TEE) revealed a large multilobulated mobile thrombus in the left atrial appendage. The patient refused warfarin therapy and instead chose to take rivaroxaban. Upon outpatient follow-up, 3 months later, no visible thrombus was appreciated on repeat TEE. This case demonstrates successful resolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, the time to resolution was shorter in patients who had rivaroxaban. Data on direct oral anticoagulants, specifically in patients with intra-cardiac thrombus, are limited [11]. In a randomized trial, rivaroxaban was more effective than warfarin in the resolution of left atrial thrombus in patients with non-valvular atrial fibrillation [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, the time to resolution was shorter in patients who had rivaroxaban. Data on direct oral anticoagulants, specifically in patients with intra-cardiac thrombus, are limited [11]. In a randomized trial, rivaroxaban was more effective than warfarin in the resolution of left atrial thrombus in patients with non-valvular atrial fibrillation [12].…”
Section: Discussionmentioning
confidence: 99%
“…The same hemodynamic condition that predisposes to the formation of thrombi in the LV is also found in the left atrial appendage. Starting from this similarity, from the favorable outcomes in patients with AF [ 119 ], and from the evidence that DOACs lead to the dissolution of atrial thrombi [ 2 , 3 , 4 ], the premises for the use of DOACs in patients with LV thrombus were outlined.…”
Section: Discussionmentioning
confidence: 99%
“…Left atrial (LA) or left atrial appendage (LAA) thrombi are identified in up to 10% of patients with AF and current guidelines recommend anticoagulant therapy for at least three weeks upon their detection [ 1 ]. Resolution of LA/LAA thrombus in patients receiving a DOAC has already been reported, even in cases with large thrombi [ 2 , 3 , 4 ]. Moreover, the X-TRA study—a comparative study between rivaroxaban and VKA—showed that rivaroxaban can be a potential option for the treatment of thrombi identified in LA/LAA in patients with AF [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…ASS (5 mg/kg, PO, SID) was used in the two dogs of the study of Hildebrandt et al [ 11 ]. Likewise, a left atrial thrombus in men was cured by administering rivaroxaban [ 36 ]. Thrombi in the left ventricle and left auricle in an American Cocker Spaniel were shown by echocardiography.…”
Section: Discussionmentioning
confidence: 99%